An analysis of trends in the use of animal and non-animal methods in biomedical research and toxicology publications - Taylor, Katy; Modi, Stephanie; Bailey, Jarrod (Frontiers in Lab on a Chip Technologies, 2024)
There have been relatively few attempts to quantitatively assess if, and in which areas, the use of non-animal methods (NAMs) is increasing in biomedical research and importantly, how this compares to the use of live animals. We conducted a bibliometric analysis of the relative publication of papers reporting the use of NAMs-only compared to those reporting the use of animals, even if they also reported the use of NAMs, over the period 2003 to 2022 across seven research areas (breast cancer, lung disease, blood cancer, heart disease, neurodegenerative diseases, diabetes and toxicology) and five regions (USA, China, France, Germany, UK).We found that the relative number of publications of research using NAMs-only has been higher than animal-based research for the last 20 years for all research areas and is growing.Research areas differed in their publication of NAMs-only based work, with breast cancer and lung disease having consistently the highest ratio of NAMs-only to animal-based publications and heart disease, diabetes and toxicology showing the greatest change over the time period. A key period of change was 2016-18. By 2022 the UK had the highest NAMs-only to animalbased research ratio than any other country for five of the seven research areas and China the lowest for six, accounting for publication rate. Tissue and in silico-based methods were the most common of all NAMs-only publications; lab-on-a-chip and stem cell models are increasing in their use but at much lower levels and rate of increase.